VALUE FROM LOCAL WISDOM TO REED MAT PRODUCT DEVELOPMENT IN AMNAT CHAROEN PROVINCE - Potharin, Somsiri; Banglua, Julalak (Fine Arts Journal: Srinakharinwirot University, 2025)
Background and Objective: This academic article aims to explore the value of local wisdom in developing reed mat products in Plakhao Subdistrict, Mueang District, Amnat Charoen Province. The study is based on William D. Lipe’s concept of cultural resource value assessment. Methods: The study applies a qualitative research approach using Lipe’s framework to analyze the cultural significance of local reed mat craftsmanship. The research focuses on the design, production process, cultural usage, and economic impact of reed mats within the local community. Key Findings: 1.Designing reed mats with local patterns enhances the product’s identity in the national market. 2.Using dyed reed fibers in the weaving process promotes skill development and value-added production. 3.The use of reed mats in religious and traditional ceremonies helps preserve cultural heritage sustainably. 4.Reed mat products generate employment and income for the local community. Implications of the Study: The findings support the promotion of cultural tourism in the area and demonstrate the diverse values of reed mats, including symbolic, academic, aesthetic, and economic significance. Conclusions and Future Study: Cultural heritage is crucial for research aimed at clarifying historical layers and fostering respect for national traditions. Applying Thai local wisdom in reed mat product development increases value derived from natural and local environmental resources, ultimately benefiting both the community and local economy.